QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)
Number of pages: 24

2010 KIDS Summer Camp - Thomas, Jenny (Coasters Association, 2010)
Each year the KIDS Summer Camps accommodates the youth and parents in five (5) municipalities across the Lower North Shore (Blanc Sablon. St. Paul’s River, St. Augustine, La Tabatiere and the Eau-Naturelle Discovery Camp in Chevery). These camps provide a safe and happy environment, a unique learning experience for all those involved, as well as assist the camp counsellors with leadership skills that will help them in their future endeavours. It is a place where youth can interact with other youth in an adventurous, natural and spiritual environment. Therefore, the continuation and expansion of the KIDS Summer Camp is an important service to the population of the Lower North Shore.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)
Number of pages: 24

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (2010)
Number of pages: 16